2020
DOI: 10.1007/s11764-020-00890-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of provider recommendations to restart vaccines after childhood cancer on caregiver intention to vaccinate

Abstract: Purpose: We studied the influence of oncology and primary care provider (PCP) recommendations on caregiver intentions to restart vaccines (e.g., catch-up or boosters) after cancer treatment. Methods: We surveyed primary caregivers ages 18 or older with a child who had completed cancer treatment 3–36 months prior (N=145) about demographics, child’s vaccination status, and healthcare factors (e.g., provider recommendations, barriers, preferences for vaccination). We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As health providers remain the most trusted source of information on vaccination for most patients (Dubé et al, 2013 ), they have an important role to play in addressing vaccine hesitancy (Potter et al, 2021 ). Prior research has not only demonstrated the importance of a provider recommendation on vaccine uptake – including among cancer patients (Kasting et al, 2019 ; Klosky et al, 2015 ; Lu et al, 2018 ; Warner et al, 2020 ), but has also shown that recommendation strength is an important factor in vaccination outcomes (Gilkey et al, 2016 ; Rosenthal et al, 2011 ). Improving the trustworthiness, quality, and consistency of provider communication regarding vaccines could therefore be an important strategy for building trust and addressing COVID-19 vaccine hesitancy among cancer survivors.…”
Section: Communication Strategies For Addressing Covid-19 Vaccine Hes...mentioning
confidence: 99%
“…As health providers remain the most trusted source of information on vaccination for most patients (Dubé et al, 2013 ), they have an important role to play in addressing vaccine hesitancy (Potter et al, 2021 ). Prior research has not only demonstrated the importance of a provider recommendation on vaccine uptake – including among cancer patients (Kasting et al, 2019 ; Klosky et al, 2015 ; Lu et al, 2018 ; Warner et al, 2020 ), but has also shown that recommendation strength is an important factor in vaccination outcomes (Gilkey et al, 2016 ; Rosenthal et al, 2011 ). Improving the trustworthiness, quality, and consistency of provider communication regarding vaccines could therefore be an important strategy for building trust and addressing COVID-19 vaccine hesitancy among cancer survivors.…”
Section: Communication Strategies For Addressing Covid-19 Vaccine Hes...mentioning
confidence: 99%
“…However, guidelines are needed to allow vaccine providers to formulate tailored recommendations. 20 In our sample, older age at enrollment increased the risk of missing vaccination. This may have been due to an earlier lack of knowledge among physicians about the risk/benefit ratio of vaccination for onco-hematological patients.…”
Section: Discussionmentioning
confidence: 73%
“…This may be of concern as cancer treatments that elevate the risks for immunological health consequences, 37 like graftversus-host disease (GvHD) [38][39][40] or prolonged immunodeficiency from immunosuppressant drugs, 41,42 can increase susceptibility to viral infections such as HPV and to related secondary cancers. 32,[43][44][45][46][47] Although Landier et al ( 2022) recently detected a similar antibody response from the HPV vaccine in cancer survivors after treatment compared to the general population, 48 inconsistent vaccination guidelines and recommendations for cancer survivors [49][50][51] may still impact HPV vaccine uptake. For instance, initiation of adolescent vaccines normally occurs 6 months after completing cancer treatment, 10,11,52 but standardized clinical guidelines for HPV vaccine initiation or resumption after cancer treatment are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although Landier et al. (2022) recently detected a similar antibody response from the HPV vaccine in cancer survivors after treatment compared to the general population, 48 inconsistent vaccination guidelines and recommendations for cancer survivors 49–51 may still impact HPV vaccine uptake. For instance, initiation of adolescent vaccines normally occurs 6 months after completing cancer treatment, 10,11,52 but standardized clinical guidelines for HPV vaccine initiation or resumption after cancer treatment are unclear 12 .…”
Section: Discussionmentioning
confidence: 99%